Paciente masculino de 70 años de edad con insuficiencia renal crónica y diálisis peritoneal - Molina Albert, Loanny Marianela (2018)
The present case study is based on a 70-year-old male patient diagnosed with chronic renal failure who performs peritoneal dialysis 3 times a week. The patient presents headache, nausea, loss of appetite and respiratory distress. It has a weight of 45kg, size of 162cm, circumference of the calf 26 cm, circumference of the arm 20 cm. The respective nutritional assessment was carried out, where we found a BMI of 17.1 kg / m2, resulting in malnutrition. The nutritional requirements were calculated, using the Harris Benedict formula, activity factor and stress factor for this pathology and we obtained a diet of 1586 kcal / day, hyposodic - controlled in phosphorus and potassium, divided into 5 meals. To avoid nutritional deficiencies and can improve your body weight. The biochemical tests show a hemoglobin of 8 mg / dl - Anemia and Albumin of 3mg / dl, indicates hypoalbuminemia, these are low. And elevated glucose 130mg / dl - hyperglycemia, urea of 60mg / dl - hyperuricemia and creatinine of 2.9mg / dl indicates kidney damage, the other tests are in their normal values. In order to avoid the extension of the number of patients with chronic renal insufficiency, we must carry adequate habits in the diet, in order to prevent the formation of different diseases that affect the population. Finally, the patient must follow the proposed diet, in order to observe improvements in their nutritional status.